CAREER EDUCATION PATHWAYS OF THE DISABLED - Satitpong Munlum สถิตย์พงษ์ มั่นหลำ; Wandee Sutthinarakorn วรรณดี สุทธินรากร; อินทจักร์ อุทุมพร (Dusit Thani College Journal, 2018)
The present study aimed at examining the formal and informal vocational institutions on their provision of career education pathways for people with disabilities. A documentary analysis was applied to obtain the data related to learning and teaching process, including the qualitative data from in-depth interview with 16 school directors and instructors, 20 disabled students at Don Bosco Technological College, Redemptorist Vocational School for People with Disabilities and 9 Vocational Rehabilitation Centers. A content analysis was then employed with the qualitative data. The findings revealed that having a career, for the disabled, is the most important base of self-worth living in a society. They do not want a “sympathy” but rather an “understanding” from others regarding their disabilities. Therefore, they wish to be given a “chance” for a career and living their lives like other people For them, a career opportunity can be a first-step exposure to “self-reliance”, which is meaningful for living their lives in a society with dignity. The curricula can be a blueprint for a learning and teaching management provide for the disabled, wherein they will learn both vocational skills and social interaction skills. However, it is suggested that the classroom teaching media be used the same with those for ordinary people in order to welcome them to a real world paralleled with a provision of medical, educational, vocational and social convalescence.